1989
DOI: 10.1164/ajrccm/139.6.1446
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Cigarette Smoking on T Cell Subsets: A Population-based Survey of Healthy Caucasians

Abstract: To investigate the influence of cigarette smoking on mononuclear cell subsets, we determined T cell, B cell, monocyte, and HLA-DR+ subsets in a population-based, stratified, random sample of healthy Caucasians using monoclonal antibodies and flow cytometry. The study population consisted of 282 subjects 20 to 69 yr of age, including 108 smokers and 174 nonsmokers. Multivariate analysis techniques were used to assess the influence of cigarette smoking status after controlling for the effects of age and gender. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

12
88
0
8

Year Published

1992
1992
2015
2015

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 179 publications
(108 citation statements)
references
References 9 publications
12
88
0
8
Order By: Relevance
“…These correlations were stronger than those with number of cigarettes smoked per day, suggesting that the BoE considered are more reliable for smoke exposure than number of cigarettes smoked per day. The observed increase in total T cells and CD4 + T cells in this study is in agreement with previous work [39,40]. CD4 + T cells appear to be responsible for the observed higher counts in circulating T cells in peripheral blood of smokers.…”
Section: Variablessupporting
confidence: 93%
See 1 more Smart Citation
“…These correlations were stronger than those with number of cigarettes smoked per day, suggesting that the BoE considered are more reliable for smoke exposure than number of cigarettes smoked per day. The observed increase in total T cells and CD4 + T cells in this study is in agreement with previous work [39,40]. CD4 + T cells appear to be responsible for the observed higher counts in circulating T cells in peripheral blood of smokers.…”
Section: Variablessupporting
confidence: 93%
“…CD4 + T cells appear to be responsible for the observed higher counts in circulating T cells in peripheral blood of smokers. In agreement with Tollerud et al, CD4/ CD8 ratio was increased in smokers [40]. Other studies have reported an elevated proportion of T lymphocytes but a lower CD4/CD8 ratio in peripheral blood of smokers [41,42].…”
Section: Variablessupporting
confidence: 90%
“…Conversely, REs were significantly more frequent in smokers (420 packyear) or patients with pre-existing lung disease. There may be several explanations for the increased rate of REs in smokers: (i) cigarette smoke might impair the clearance and detoxification of bacteria, resulting in a higher prevalence of bacterial colonization of proximal or distal airways; 16,17 (ii) smoking is associated with immunologic disturbances; 18,19 (iii) in healthy long-term smokers, myocardial blood flow is impaired and the degree of impairment correlates with the number of years the patient has smoked; 20,21 and (iv) in animal models, cigarette smokes impairs cardiopulmonary function and increases capillary permeability. This could explain the hydration-related pulmonary edema occurring at the onset of chemotherapy.…”
Section: Respiratory Events In Acute Leukemia D Chaoui Et Almentioning
confidence: 99%
“…Nach Aus sa ge ei ni ger Stu di en führt Rauchen zu ei ner all ge mei nen Er hö hung der Leu ko zy ten, ein schließ lich der CD4+ und CD8+ Lym pho zy ten, und zwar in Ab hän-gig keit vom Ta b ak kon sum [65,92,93,94,95,96,97,98,99]. Ein Ein fluss auf das Verhält nis der nai ven (CD45RA+) und Memo ry-T-Zel len (CD45RO+) wur de nicht be ob ach tet.…”
Section: Ta Bakrauchunclassified
“…In ei ner an de ren Stu die fanden sich kei ne sig ni fi kan ten Ver än de rungen der Mo no zy ten, Gra nu lo zy ten und NK-Zel len oder CD3+ und CD19+ Zel len [100]. Mil li et al [101] und Tol le rud et al [96,97] be schrie ben da ge gen, dass die abso lu te Zahl von B-Zel len bei star ken Rauchern an steigt, wäh rend die NK-Zel len deut lich ab sin ken.…”
Section: Ta Bakrauchunclassified